2021
DOI: 10.1042/bsr20203461
|View full text |Cite
|
Sign up to set email alerts
|

The correlation ofmicroRNA-499rs3746444 T>C locus with the susceptibility of gastric cancer: from a case–control study to a meta-analysis

Abstract: The relationship between rs3746444 T>C single-nucleotide polymorphism (SNP) in microRNA (mir)-499 and risk of gastric cancer (GC) has been widely investigated. However, the association was still unconfirmed. Here, we first recruited 490 GC patients and 1476 controls, and conducted a case-control study. And we did not find any association between rs3746444 T>C SNP polymorphism and risk of GC. Subsequently, we conducted a meta-analysis to explore the association of mir-499 rs3746444 polymorphism wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Another study reported that although there was no significant association between miR-27a rs895819 and gastrointestinal tumor risk, this SNP could synergize with other risk factors to increase the risk of gastrointestinal tumors ( Shankaran et al, 2020 ). Meanwhile, several studies have found that there are different degrees of associations between miR-499 rs3746444, miR-149 rs2292832, miR-146a rs2910164 and GC risk ( Zhang et al, 2018 ; Rong et al, 2021 ; Liang et al, 2022 ). And as we know, the occurrence and development of many diseases is a complex processes involving multifactor, multigene and multistage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that although there was no significant association between miR-27a rs895819 and gastrointestinal tumor risk, this SNP could synergize with other risk factors to increase the risk of gastrointestinal tumors ( Shankaran et al, 2020 ). Meanwhile, several studies have found that there are different degrees of associations between miR-499 rs3746444, miR-149 rs2292832, miR-146a rs2910164 and GC risk ( Zhang et al, 2018 ; Rong et al, 2021 ; Liang et al, 2022 ). And as we know, the occurrence and development of many diseases is a complex processes involving multifactor, multigene and multistage.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Genetics frontiersin.org (Zhang et al, 2018;Rong et al, 2021;Liang et al, 2022). And as we know, the occurrence and development of many diseases is a complex processes involving multifactor, multigene and multistage.…”
Section: Discussionmentioning
confidence: 99%
“…The association of miRNA-499 with cancers of the GI tract has concentrated on examining the relationship between Single nucleotide polymorphisms (SNPs) in miRNA-499 rs3746444 and susceptibility to GI tract tumorigenesis. Investigators have found that specific polymorphisms can increase the risk of ESCC ( 244 ), GC ( 245 ) and CRC ( 246 ) or have no effect on GI cancer susceptibility ( 247 , 248 ).…”
Section: The Relationship Between Specific Micrornas and Pdcd4 Expres...mentioning
confidence: 99%
“…In addition, various research groups have been analyzing the role of genetic polymorphisms of miRNAs in GC under the rationale of hypothesis-driven (candidate gene) approach [ 15 ]. These studies, mostly conducted in Asia, evidenced the role of miRNA and its polymorphisms as potential new targets for diagnosis and treatment of GC [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Unfortunately, in the Latin American population, in particular in the Chilean population which has one of the highest GC mortality rates [ 1 , 2 , 3 ], no studies have been conducted in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we analyzed all genetic polymorphisms of miRNAs deposited in miRBase, including those which have already been evaluated in other studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Here, we identified seven previously unreported genetic polymorphisms: rs4822739 in miR-548j, rs701213 in miR-4427, rs15538677 in miR-4274, rs12416605 in miR-938, rs1439619 in miR-3175, rs61449511 in miR-6891, rs404337 in miR-8084, and rs7500280 in miR-4719.…”
Section: Introductionmentioning
confidence: 99%